فلسفہ اخلاق کا ارتقائی جائزہ،اخلاقیات کی الہامی بنیادوں کے تناظرمیں: A Critical Review of Ethical philosophy, in the Context of Inspirational Foundation of Ethics - Gulam Mustafa; Dr. Saeed Ur Rahman; Hamid Rabbani (Al Manhal Research Journal, 2024)
The concept of ethics has been lying in human consciousness since the very beginning. The story of Adam and Eve, the tale of the murder of Cain and Abel, is echoed in various religions under different names. This demonstrates that the concept of good and evil has been present since the dawn of humanity. The evidence of ethical teachings is found primarily in the literature of various religions of the Greeks. The Greeks had wise sayings and aphorisms dating back to pre-Christian times, which discussed human character and ethics. While every religion has articulated a few ethical principles, Islam is the only religion which has presented a complete code of ethics. It has provided aiding principles for the refinement of human life in every aspect, including marriage, livelihood, cleanliness, manners, and other human activities. Adhering to these teachings enhances an individual's personal, political, and societal and family life. Within humans lies the desire of the self, and it is essential for humans to possess a motive that enables them to decide, in its light, that by suppressing their desires, they can become productive members of society and live in harmony with others. If the concept of ethics were to disappear from any society, it would fall prey to chaos and destruction, whereas societies that uphold ethical values are the guarantors of success not only in this world but also the hereafter.